COMPARISON OF HYPERTENSION, ITS CONTROL AND COMPLIANCE OF ANTI-HYPERTENSIVES AMONG DEPRESSED AND NON-DEPRESSED PATIENTS - Iqbal, Muhammad Asif; Khalil, Ayesha; Subhan, Saad; Khan, Marina; Gul, Adnan (Journal of Postgraduate Medical Institute, 2021)
Objective: To compare frequency of hypertension, control of blood pressure and compliance to anti-hypertensives among depressed versus non-depressed patients. Methodology: This cross-sectional study was conducted in the Department of Cardiology Lady Reading Hospital, Peshawar. The patients were interviewed for the diagnosis of depression and compliance to anti-hypertensives. PHQ 9 questionnaire was used to diagnose depression among study patients. Total patients were 1026 divided into two groups, group A were 634 patients and group B were 392 patients. Group A were patients having moderate, moderately severe and severe depression and Group B patients were having no depression and mild depression. The two groups were compared for the frequency of hypertension, and compliance to drugs using Morisky medication adherence scale. SPSS v.20.0 was used to analyze the data. Results: The mean age of the sample was 55.86±11.37 years with male to female ration of 1.5:1. Hypertension was present in 69.24% of patients in group A and 60.46% group B (p=0.006). Mean SBP was 131.17+24.7 mmHg in depressed patients and 124.20+19.7 mmHg in non-depressed (p=0.000). Similarly mean DBP was 82.06+13.3 mmHg in depressed and 78.99+12.1 mmHg in non-depressed patients (p=0.004). 335/392 non-depressed patients were compliant to medication as compared to 512/634 depressed patients (p=0.052). Conclusion: Hypertension was found to be more prevalent among depressed patients. In compliance to anti-hypertensives, depressed patients had lesser compliance than the patients of the other group.